Temporal evolution of dermonecrosis in loxoscelism assessed by photodocumentation - Borrasca-Fernandes,Carla Fernanda (2022)
ABSTRACT Background: Although loxoscelism (bites by brown spiders of the genus Loxosceles) frequently results in dermonecrosis, no previous clinical reports have provided detailed temporal photodocumentation of the evolution of dermonecrotic lesions in a case series. Methods This was a retrospective cohort study involving a case series of loxoscelism. Only cases of dermonecrosis with photodocumentation of lesion evolution (from admission until complete or almost complete healing) were included. Results: Eight patients (six men, two women; median age, 38 years) fulfilled the inclusion criteria. The bite sites included the thigh (n = 4), forearm (n = 2), abdomen (n = 1), and trunk (n = 1). Time interval between the bite and first contact with our service ranged from 15 to 216 h (median = 29 h). The main clinical manifestations included local erythematous and ischemic violaceous lesions overlying a base of indurated edema (livedoid plaque, 8), local pain (8), exanthema (6), serohemorrhagic vesicles/blisters (5), fever (5), and jaundice (1). Based on a previously established classification, the cases were classified as probable cutaneous-necrotic loxoscelism (CNL, n = 4), presumptive CNL (n = 3), and presumptive cutaneous-hemolytic loxoscelism (n = 1). Seven patients were treated with anti-arachnidic antivenom (AV; median time post-bite = 46 h). Complete lesion healing ranged from 34 to 98 days post-bite (median, 68 days; six patients). None of the patients required reconstructive plastic surgery. Conclusions The sequential photographic documentation showed considerable variation in the process of wound healing, with complete epithelialization requiring up to 3 months after the bite.